2006
DOI: 10.1007/s00251-006-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene structure and transcription of IRF-2 in the mandarin fish Siniperca chuatsi with the finding of alternative transcripts and microsatellite in the coding region

Abstract: The gene of interferon regulatory factor-2 (IRF-2) has been cloned from the mandarin fish (Siniperca chuatsi). The IRF-2 gene has 6,418 nucleotides (nt) and contains eight exons and seven introns, encoding two mRNAs. The two IRF-2 mRNAs each contained an open reading frame of 873 nt, which both translate into the same 291 amino acids but differed in their 5′ untranslated region: one mRNA was transcribed initially from the exon 1 bypassing exon 2, while the other was transcribed from the exon 2. The microsatell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…When injected with polyI:C or LPS, the increased expression is in immune-related tissues, especially in head kidney. These results are consistent with other fish IRF-2 gene expression patterns, such as mandarin fish and snakehead fish (Sun et al, 2006;Jia and Guo, 2008). However, in the gill, the EcIRF-2 gene has a low expression level compared to those fish, and the decreased expression following stimulation of polyI:C or LPS appeared in both orange-spotted grouper and mandarin fish.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When injected with polyI:C or LPS, the increased expression is in immune-related tissues, especially in head kidney. These results are consistent with other fish IRF-2 gene expression patterns, such as mandarin fish and snakehead fish (Sun et al, 2006;Jia and Guo, 2008). However, in the gill, the EcIRF-2 gene has a low expression level compared to those fish, and the decreased expression following stimulation of polyI:C or LPS appeared in both orange-spotted grouper and mandarin fish.…”
Section: Discussionsupporting
confidence: 89%
“…IRF-2 also has an unexpected role in the regulation of apoptosis and cell growth (Cuesta et al, 2003). Due to the significant differences between mammals and fish, much effort has been made to study fish IRF family in recent years, and a few members have been reported, such as IRF-1, IRF-2, IRF-3 and IRF-7 (Holland et al, 2008;Kileng et al, 2009;Caipang et al, 2009;Jia and Guo, 2008;Sun et al, 2006;Collet et al, 2003;Zhang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…At present, fish IRF-1, IRF-2 and IRF-7 genes are shown to be induced by virus, IFN or poly I:C in several species (Collet et al, 2003a,b;Ordas et al, 2006;Sun et al, 2006Sun et al, , 2007Zhang et al, 2003). Our findings also indicated that poly I:C can induce the expression of CaIRF genes in snakehead spleen and liver.…”
Section: Discussionmentioning
confidence: 99%
“…Among teleost IRFs, IRF-1 has been cloned and characterized from flounder (Paralichthys olicaceus), pufferfish (Fugu rubripes), rainbow trout (Oncorhynchus mykiss), turbot (Scophthamus maximus) and sea bream (Sparus aurata) (Yabu et al, 1998;Richardson et al, 2001;Collet et al, 2003a,b;Ordas et al, 2006). IRF-2 has been reported in rainbow trout and mandarin fish (Siniperca chuatsi), and homologous to known vertebrate IRF-2 (Collet et al, 2003a,b;Sun et al, 2006). Moreover, IRF-7 has been cloned from goldfish (Carassius auratus) and mandarin fish (Zhang et al, 2003;Sun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation